An Evaluation of Some Risk Factors and ABO Blood Groups in Breast Cancer Patients - Abdul-Jabbar, Rawaa; Ad’hiah, Ali; Ghaloub , Abdalamer (Iraqi Journal of Science, 2024)
The study involved 120 women, who were distributed into two groups of breast tumor patients (30 malignant and 30 benign) and a group of controls (60 women). The patients were referred to the Center for Early Detection of Breast Tumor at Al-Alwayia Hospital for Gynecology and Obstetrics (Baghdad) during the period June-December 2011. They were investigated for the frequency of ABO blood group phenotypes, menopausal status, oral contraceptive use, body mass index and family history of breast cancer or other cancers. The results demonstrated that 60.0% of malignant cases clustered after the age 50 years, while it was 20.0% in benign cases. Fifty percent of malignant breast tumor patients reached menopause, while in benign cases, the corresponding frequency was much lower (20.0%). It was also observed that 60.0% of malignant patients used oral contraceptives, while such frequency was lower in benign patients (20.0%). Overweight and obese cases were observed with a frequency of 43.3 and 26.7%, respectively in malignant patients, and the corresponding frequencies in benign patients were 36.7 and 33.3%, respectively. Positive family history of malignant breast cancer accounted for 43.3% in malignant cases, while in benign cases; it was less frequent (20.0%). The distribution of ABO blood group phenotypes demonstrated a significant difference (P ≤ 0.05) between malignant patients and controls, but not between benign patients and controls. Such significant difference was mainly contributed by an increased frequency of B phenotype (36.7 vs. 16.7%) and a decreased frequency of O phenotype (26.7 vs. 55.0%) in malignant patients.